Sustainable territorial development strategy for the impact of mining megaprojects: a study of four intermediate cities in Chile, Latin America - Contreras-Rojo, Carlos; Ortega-Pineda, Gonzalo (Revista de Estudios Andaluces, 2024)
The Chilean economy finds one of its pillars in mining, a sector that plays a crucial role. Currently, it contributes 9.4% to the national Gross Domestic Product (GDP) and holds the dominant position in foreign investment, with an impressive 33.3% of the total. Globally, this industry leads in the production of minerals such as copper, rhenium, natural nitrates, lithium, and iodine. There is a lack of studies on the transformation that the urban centers known as “intermediate cities,” have undergone at the regional level, given that productive mining industries have altered the local reality. In this process, urban development patterns have been largely shaped by an economic logic focused on the supply of services and products, sometimes at the expense of the well-being standards of the inhabitants. Studying the effects of the mining industry on these urban centers allows for an understanding of the economic logics present in the region, with the aim of generating a model of urban planning that can mitigate negative socio-spatial consequences, introducing environmental factors characteristic of sustainable cities as a method of projecting mining urban centers beyond finite production cycles (Bithas & Christofakis, 2006). This involves activating social, environmental, and cultural resources for sustainable development that ensures the permanence of its inhabitants (Van Kessel, 2003). The analysis was approached at the local level, studying the impact that mega-mining projects have had on Chilean cities, taking four emblematic cases of settlements linked to mineral production and service provision that have been affected by exponential growth in size due to the demands of extractive operations and their human capital. Faced with uncontrolled expansion, a development model based on sustainability principles is proposed for the strategic management of the basic resources of cities to avoid compromising their future.